If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -35 = x + 18 Reorder the terms: -35 = 18 + x Solving -35 = 18 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -35 + -1x = 18 + x + -1x Combine like terms: x + -1x = 0 -35 + -1x = 18 + 0 -35 + -1x = 18 Add '35' to each side of the equation. -35 + 35 + -1x = 18 + 35 Combine like terms: -35 + 35 = 0 0 + -1x = 18 + 35 -1x = 18 + 35 Combine like terms: 18 + 35 = 53 -1x = 53 Divide each side by '-1'. x = -53 Simplifying x = -53
| 4x+4=-20-2x | | 3/5--2/5= | | 60+p=70 | | 6s-4=-20 | | y=3/4*3+1 | | 4a+1-8a=9 | | 8mn-5m= | | 3l+y=5+5l | | 88-8m=8m+88 | | -16.5h+9.25h=21.75 | | -13y-34y= | | y=3/4(3)+1 | | 2m+3m-6=7m-34 | | 46+y=136 | | 14mn-19mn= | | 3x=7y-2 | | 4y-15y=22 | | 10y^2+28y-5=0 | | -x-45=47 | | 5a^2-17+14=0 | | 9+d=23 | | 4(7-4k)+2k=-36-6k | | 2+4(x-5)=5 | | 2(3.5)+2w=31 | | x+20+x+10=180 | | 1.2-17= | | 1x+(-1)-3-1x=3+1x-2-(-1)-1x | | 3x+7x+1=2(5x+1)+3 | | 4a+6b+2=2a-4b | | -1=-1/3(1)+b | | 64x-88x= | | x+3(.4)=5 |